Development of Zinc Oxide Sensors for Detecting Ammonia Gas in the Ambient Air: A Critical Short Review. Issue 1 (December 2016) - Chatterjee, Bappaditya; Bandyopadhyay, Amitava
Abstract : Ammonia (NH3 ) is emitted into the atmosphere by various industries and other sources and causes environmental pollution. Considering the hazards of ammonia, detecting leakage from vessels and pipes demands the use of sensors. Therefore, the development of NH3 gas sensors assumes considerable importance to researchers and regulators and to industry, businesses, and facilities that make, store, or use ammonia. The use of metal oxide sensors (MOS) for detecting NH3 gas, such as zinc oxide (ZnO), has been a topic of interest to researchers seeking methods to detect NH3 gas, even at low concentrations. In this article, an attempt has been made to review the research thus far published on the synthesis of ZnO‐based NH3 gas sensor materials, their characterization, and analyses of their performance. Finally, we make several recommendations regarding the scope of future research. For example, the kinetics of the sensor materials should be determined. Furthermore, extensive studies of gas–solid (NH3 –ZnO) adsorption are proposed to ascertain the exact adsorption mechanism in terms of isotherm, kinetics, and diffusive mass transport, and to determine "reversibility" and "recovery" of sensor materials so they can continue sensing and activating alarms when necessary for practical applications.